2020
DOI: 10.1136/jitc-2020-001007
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes to first-line pembrolizumab in patients with PD-L1-high (≥50%) non–small cell lung cancer and a poor performance status

Abstract: BackgroundPatients with non–small cell lung cancer (NSCLC) and a poor Eastern Cooperative Oncology Group Performance Status (ECOG PS) have been excluded from phase III immunotherapy clinical trials. We sought to evaluate clinical outcomes to first-line pembrolizumab in patients with advanced NSCLC, a PD-L1 Tumor Proportion Score (TPS) of ≥50%, and an ECOG PS of 2.MethodsWe performed a multicenter retrospective analysis of patients with metastatic NSCLC and a PD-L1 TPS of ≥50% (negative for genomic alterations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 17 publications
8
14
0
Order By: Relevance
“…Subgroup analyses in patients with an ECOG PS score at least 2 and tumor PD-L1 TPS of at least 50%, any tumor PD-L1 TPS treated with pembrolizumab in the first-line setting, and tumor PD-L1 TPS of at least 50% who were treated with pembrolizumab in the first-line setting showed results consistent with prior studies, with the major exception of shorter OS in our cohort compared with the Pembrolizumab in Patients With Non–Small Cell Lung Cancer of Performance Status 2 (PePS2) trial 7 , 14 , 15 , 16 , 17 (eTable 3 in the Supplement ). Further analysis of patients belonging to the group with ECOG PS scores of at least 2 who achieved vs did not achieve durable clinical benefit (defined as PFS >6 months) revealed no differences in baseline clinicopathological characteristics (eTable 4 in the Supplement ); however, those with durable clinical benefit had a higher likelihood of developing any grade immune-related adverse events than those without durable clinical benefit (5 [71.4%] vs 4 [18.2%]; P = .02).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Subgroup analyses in patients with an ECOG PS score at least 2 and tumor PD-L1 TPS of at least 50%, any tumor PD-L1 TPS treated with pembrolizumab in the first-line setting, and tumor PD-L1 TPS of at least 50% who were treated with pembrolizumab in the first-line setting showed results consistent with prior studies, with the major exception of shorter OS in our cohort compared with the Pembrolizumab in Patients With Non–Small Cell Lung Cancer of Performance Status 2 (PePS2) trial 7 , 14 , 15 , 16 , 17 (eTable 3 in the Supplement ). Further analysis of patients belonging to the group with ECOG PS scores of at least 2 who achieved vs did not achieve durable clinical benefit (defined as PFS >6 months) revealed no differences in baseline clinicopathological characteristics (eTable 4 in the Supplement ); however, those with durable clinical benefit had a higher likelihood of developing any grade immune-related adverse events than those without durable clinical benefit (5 [71.4%] vs 4 [18.2%]; P = .02).…”
Section: Resultssupporting
confidence: 89%
“…Other retrospective studies have focused on a further selected subgroup of patients with advanced NSCLC with PD-L1 TPS of at least 50% and ECOG PS scores of 2 treated with first-line pembrolizumab monotherapy. 14 , 15 , 16 Results from the subgroup analysis in our cohort mirror the results reported from the largest study of such patients, 14 which reported a median PFS and OS of 2.4 months and 3.0 months, respectively (eTable 3 in the Supplement ).…”
Section: Discussionsupporting
confidence: 81%
“…These results highlight differences between patients in clinical practice and those in clinical trials, which are limited to providing information from select and relatively well-performing patients. Regardless of treatment regimen, patients with ECOG PS >1 had shorter median OS, which was reported previously from studies of 1L I-O monotherapy in patients ≥50 % tumor PD-L1 expression [28][29][30]. Older age was associated with shorter median OS regardless of treatment regimen in patients with non-squamous NSCLC but not in those with squamous histology.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, patients with brain metastases have an mOS comparable to that of patients without brain metastases [ 13 , 14 ]. By contrast, PS ≥ 2 has been associated with significantly reduced mOS, independent of treatment line, and a systematic review demonstrated a pooled mOS hazard ratio (HR) of 2.72 compared to PS 0–1 [ 15 , 16 ]. RWS indicate significantly reduced response rates and impaired mOS in patients with bone metastases (BoM) compared to those without [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%